Analisa Yuridis Tentang Perjanjian Sewa Menyewa Tanpa Batas Waktu - Darmawan, Marchelo Ivan; Suryawati, Nany (Faculty of Law, Diponegoro University, 2023)
Land is one of the primary human needs that is needed in various human activities in carrying out their lives, but land is a limited natural resource that cannot increase in number. Population growth is increasing but the supply of natural resources in the form of land cannot increase, this makes land a scarce resource and increasingly difficult to obtain because the price increases every year so that the community has another option, namely by taking legal action in the form of leasing land and / or buildings. The Civil Code and the Law of Treaties in Indonesia do not contain rules regarding time limits in leases, so the author is interested in conducting a juridical analysis of indefinite lease agreements and how to regulate the termination of indefinite lease agreements in Indonesia. This article uses a normative juridical approach method with a legislative approach and a conceptual approach, the legal materials used are primary and secondary materials. The result of the analysis is that an indefinite land lease agreement can be made because in the Civil Code, Law Number 5 of 1960 concerning Basic Regulations of Agrarian Principles there is no specific regulation regarding the time limit of the lease agreement, then the indefinite lease agreement can be terminated with the agreement of both parties and must notify the tenant in advance if they want to stop the lease.